ANALISIS KESALAHAN SISWA DALAM MENYELESAIKAN SOAL CERITA MATEMATIKA MATERI PECAHAN BERDASARKAN TEORI NEWMAN PADA SISWA SD - Reni Wahyuni Syahrul; kristiawati; Baharullah (STKIP Subang, 2025)
This study aims to describe students' errors in solving mathematics problems on the topic of fractions based on Newman’s Error Analysis. The background of this research is the low learning outcomes of fifth-grade students in the fractions topic at SD Inpres Tamamaung III. This research employs a descriptive qualitative method. Data were collected through written tests and interviews. Out of 29 fifth-grade students, three subjects were selected based on their level of error according to Newman’s procedure, categorized into high, medium, and low error levels. The student with a high level of error made several mistakes, including comprehension errors, transformation errors, process skills errors, and errors in writing the final answer. The student with a medium level of error committed transformation errors, process skills errors, and final answer writing errors. Meanwhile, the student categorized as having a low level of error made no mistakes and answered the questions correctly. The results of the study indicate that most students made errors in solving word problems based on Newman’s procedure, including reading errors, comprehension errors, transformation errors, process skills errors, and final answer writing errors. To validate the test results, the researcher conducted interviews with the three selected subjects representing the different levels of errors. These errors were caused by students’ lack of accuracy, difficulty in understanding concepts, and a tendency to rush through the tasks.